Two new species of Jogocerus Viraktamath (Hemiptera: Cicadellidae: Idiocerinae) from China - Xue, Qingquan; Zhang, Yalin (Zootaxa, 2017)
Two new species, Jogocerus concavus sp. nov. and J. viraktamathi sp. nov. are described and illustrated. The genus Jogocerus is redescribed together with a checklist and key to species for the separation of males.